Muscle and skin necrotizing and edema-forming activities of Duvernoy’s gland secretion of the xenodontine colubrid snake Philodryas patagoniensis from the North-east of Argentina - Peichoto, Peichoto, María Elisa (2004)
Fil: Peichoto, Peichoto, María Elisa. Universidad Nacional Del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura; Argentina.